2006
DOI: 10.1109/lpt.2006.873359
|View full text |Cite
|
Sign up to set email alerts
|

Steep and adjustable transfer functions of monolithic SOA-EA 2R regenerators

Abstract: Abstract-Measurements and numerical modeling of a reamplification and reshaping (2R) regenerator demonstrate a steep power transfer function with adjustable threshold. The threshold can be adjusted more than 6 dB by simple control of the reverse bias voltage of the absorber section. The device consists of a semiconductor waveguide with alternating amplifier and absorber sections using quantum-well active material. The steep nonlinearity of the transfer function is achieved by concatenating several sections. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The gain saturation model used in this work has proved to result in less nonlinear behavior than experiments [11]. It has also been shown that a more detailed model for the saturation of SOAs that takes into account counterpropagating ASE and includes nonzero facet reflectivities predicts a stronger nonlinearity [23]. In such a case of stronger nonlinearity, the role of higher order noise correlations is expected to be even more important.…”
Section: Numerical Examples and Discussionmentioning
confidence: 83%
“…The gain saturation model used in this work has proved to result in less nonlinear behavior than experiments [11]. It has also been shown that a more detailed model for the saturation of SOAs that takes into account counterpropagating ASE and includes nonzero facet reflectivities predicts a stronger nonlinearity [23]. In such a case of stronger nonlinearity, the role of higher order noise correlations is expected to be even more important.…”
Section: Numerical Examples and Discussionmentioning
confidence: 83%
“…This saturation region can be used to decrease the noise at "1" level. In fact, the gain saturation of the SOA was used to suppress the noise at "1" level, as shown by Öhman et al [7] and Vivero et al [8] . We also simulate dynamic 2R operation at 10 Gbit/s.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…2R regeneration can also be realized by using Four-Wave Mixing in an SOA [4] , but this scheme has a low optical signal-to-noise ratio and requires high operating optical power. In addition, an SOA and an electro-absorber are utilized for 2R regeneration [5][6][7][8] , where cross-gain compression in an SOA is used to suppress the noise at "1"-level, saturable absorption in the absorber is used to suppress the noise at "0"-level.Integration version of this concept was presented [8] . This structure has a complicated configuration and the absorber induces a considerable loss.…”
mentioning
confidence: 99%
“…Therefore, monolithic integration of SOA and EAM can be used for taking both advantages, improving the function of all-optical 2R regeneration. The cascaded SOA and EAM elements have been proposed for high on-off ratio in nonlinear transfer function for 2R [5][6]. However, the intrinsic carrier dynamic of saturation behaviors in both SOA and EAM devices will inevitably cause pattern-dependent problem, limiting the usage of high-speed data transmission.…”
Section: Introductionmentioning
confidence: 99%